2012
DOI: 10.1155/2012/326731
|View full text |Cite
|
Sign up to set email alerts
|

Bicarbonate Plays a Critical Role in the Generation of Cytotoxicity during SIN-1 Decomposition in Culture Medium

Abstract: 3-Morpholinosydnonimine (SIN-1) is used as a donor of peroxynitrite (ONOO−) in various studies. We demonstrated, however, that, the cell-culture medium remains cytotoxic to PC12 cells even after almost complete SIN-1 decomposition, suggesting that reaction product(s) in the medium, rather than ONOO−, exert cytotoxic effects. Here, we clarified that significant cytotoxicity persists after SIN-1 decomposes in bicarbonate, a component of the culture medium, but not in NaOH. Cytotoxic SIN-1-decomposed bicarbonate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…However, very similar cytotoxic effects supporting our observations were reported in the case of neural PC12 cells exposed to peroxynitrite generated during oxidation of 3-morpholinisydnonimide (SIN-1) (Konishi et al, 2009; Shirai et al, 2012). The exposure of cells to the culture medium obtained after complete SIN-1 decomposition demonstrates almost the same level of cytotoxicity as fresh SIN-1.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, very similar cytotoxic effects supporting our observations were reported in the case of neural PC12 cells exposed to peroxynitrite generated during oxidation of 3-morpholinisydnonimide (SIN-1) (Konishi et al, 2009; Shirai et al, 2012). The exposure of cells to the culture medium obtained after complete SIN-1 decomposition demonstrates almost the same level of cytotoxicity as fresh SIN-1.…”
Section: Discussionsupporting
confidence: 90%
“…The authors concluded that the formation of toxicants is a result of the simultaneous formation of NO and superoxide. In agreement with our considerations regarding the mechanism of peroxynitrite reactivity, it was found that CO 2 plays a critical role in the cytotoxicity of the SIN-1 decomposition products (Shirai et al, 2012). Surprisingly, the authors misinterpreted the effect of BSA when they found that addition of fresh serum (or BSA) antagonizes the cytotoxicity.…”
Section: Discussionsupporting
confidence: 90%
“…Next, fluorescence imaging was carried out for intracellular ONOO – . Cells were pretreated with 3-morpholinosydnonimine hydrochloride (SIN-1, a known ONOO – donor); in a control group, uric acid (UA, a known ONOO – scavenger) was pretreated with cells to quench ONOO – . We observed that when cells were pretreated with SIN-1, the fluorescence of the probe in both HepG2 (Figure ) and RAW 264.7 (Figure S5) cells enhanced significantly with respect to the control group.…”
Section: Resultsmentioning
confidence: 95%
“…The reaction was run at 30-min intervals for three trials. The oxygen consumption was expressed as percentage of oxygen consumed [19]. The reagents were mixed according to the following experimental conditions: 1…”
Section: Measurement Of Oxygen Consumptionmentioning
confidence: 99%
“…4b). It has become increasingly evident that carbon dioxide plays a critical role in the formation of the peroxynitrite during SIN-1 auto-oxidation as it can directly react with peroxynitrite [19]. Thus, we further examined the effects of bicarbonate on SIN-1-mediated oxygen consumption in the presence of 5-ASA.…”
Section: Statistical Analysesmentioning
confidence: 99%